Levelled-container: a new utility for determining the testicular volume in small ruminants - Harighi, Mohammadfazel; Haron, Abd Wahid; Abdullah, Faez Firdaus Jesse; Thomson, P. C.; Yusop, Mohd Rafii (Faculty of Animal Husbandry, Brawijaya University, 2017)
This study is conducted to assess the validity of a designed utility, suitable for measuring testicular volume. We describe a beaker, equipped with two vial levels, based on a water displacement method, known as a “levelled container” for measuring testicular volume. Testicular volumes of 47 Boer bucks were measured using two different tools, namely an overflow vessel and a levelled container as the standard and targeted equipment respectively. A Passing-Bablok regression analysis (to assess linearity) and a Bland-Altman method plot were performed to assess the validity of testicular volume measurement of the levelled-container method compared with that from the overflow vessel. The results indicated that the levelled-container is a valid utility and its results have a significant linear association with the estimated testicular volume from the overflow vessel. In conclusion, the levelled container can be recommended as an alternative method to measure testicular volume in goats, particularly because of its ease of use.